Health practitioner practices and their influence on nutritional intake of hospitalised patients - Andrea P. Marshall; Tahnie Takefala; Lauren T. Williams; Alan Spencer; Laurie Grealish; Shelley Roberts (Elsevier, 2019)
Objectives: In the hospital setting, poor dietary intake interacts with disease and represents a major and modifiable cause of malnutrition. Understanding barriers to adequate dietary intake is an important strategy to guide the development of interventions to improve nutrition intake. The aim of this study reported in this paper was to explore patient, family and health care professionals' perceptions of barriers to and enablers of adequate nutrition care and dietary intake of medical inpatients. Methods: An exploratory qualitative study design incorporating group and individual interviews of patients (n = 14), their family members (n = 4), and health care professionals (n = 18) was undertaken. Participants were recruited pragmatically, using a mix of convenience and purposive sampling. A theoretically informed, semi-structured interview schedule was based on observations of practice and the Theoretical Domains Framework. Interviews were audio-recorded, transcribed verbatim and analysed inductively using a general inductive approach. Results: Three key themes emerged from analysing participant interviews. Siloed approaches to nutrition care reflected the diverse range of health care professionals responsible for nutrition care but who often worked in isolation from their colleagues. Competing work priorities for nurses reflected the challenge in prioritise nutrition care which was often constrained because of other care needs or work-related pressures. Helping patients to eat highlighted that nurses were often the only health care professional who would provide assistance to patients at mealtimes and lack of available staff could negatively influence patients' nutrition intakes. Conclusions: We have identified many complex and interrelated barriers which preclude adequate dietary intake in acute medical patients. These predominantly reflect issues inherent in the hospital culture and environment. Multi-faceted and sustainable interventions that support a facilitating nutrition culture and multidisciplinary collaboration, inclusive of patients and families, are needed to address these underlying barriers. Keywords: Cognition, Dietary services, Patients, Personnel, Hospital, Qualitative research